Metastatic phenotype and immunosuppressive tumour microenvironment in pancreatic ductal adenocarcinoma: Key role of the urokinase plasminogen activator (PLAU) - Hosen, S. M. Zahid; Uddin, Md. Nazim; Xu, Zhihong; Buckley, Benjamin J.; Perera, Chamini; Pang, Tony C. Y.; Mekapogu, Alpha Raj; Moni, Mohammad Ali; Notta, Faiyaz; Gallinger, Steven; Pirola, Ron; Wilson, Jeremy; et al. (Frontiers in Immunology, 2022)
Results: Previous studies have revealed the role of dysregulated urokinase plasminogen activator (encoded by PLAU) expression and activity in several pathways associated with cancer progression. However, systematic investigation into the association of PLAU expression with factors that modulate PDAC (pancreatic ductal adenocarcinoma) progression is lacking, such as those affecting stromal (pancreatic stellate cell, PSC)-cancer cell interactions, tumour immunity, PDAC subtypes and clinical outcomes from potential PLAU inhibition. Our analyses revealed that PLAU upregulation is not only associated with numerous other prognostic markers but also associated with activation of various oncogenic signalling pathways, aggressive phenotypes relevant to PDAC growth and metastasis, such as proliferation, epithelial-mesenchymal transition (EMT), stemness, hypoxia, extracellular cell matrix (ECM) degradation, upregulation of stromal signatures, and immune suppression in the tumour microenvironment (TME). Moreover, upregulation of PLAU was directly connected with signalling pathways known to mediate PSC-cancer cell interactions. Furthermore, PLAU upregulation was associated with the aggressive basal/squamous phenotype of PDAC and significantly reduced overall survival, indicating that this subset of patients may benefit from therapeutic interventions to inhibit PLAU activity. Our studies with a clinically relevant orthotopic pancreatic model showed that even short-term PLAU inhibition is sufficient to significantly halt tumour growth and, importantly, eliminate visible metastasis. Conclusion: Elevated PLAU correlates with increased aggressive phenotypes, stromal score, and immune suppression in PDAC. PLAU upregulation is also closely associated with the basal subtype type of PDAC; patients with this subtype are at high risk of mortality from the disease and may benefit from therapeutic targeting of PLAU.